Pelatihan dan Pendampingan Penulisan Karya Tulis Ilmiah untuk Mengembangkan Keprofesionalan Guru Sekolah Dasar - Dwi Cahaya Nurani; Yanuar Akhmad; Fahmi Surya Adikara; Mar’atul Faida; Ana Tri Dewi Maghfiroh; Toni Aji; Dede Permana (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2021)
The teacher's profession requires writing skills to support career development and to keep learning so that teachers are obliged to write scientific papers. However, in reality, the willingness and ability of teachers to write scientific papers still need to be improved. Community Service aims to improve the ability of elementary school teachers in Batang and surrounding districts to improve their ability to write papers, which we focus on Class Action Research (CAR). The method used is through workshops and scientific papers assistance for elementary school teachers in Batang and surrounding districts. This community service activity is divided into two stages, namely the first stage of material exposure by trainers on scientific papers. The second stage is the scientific paper's activities conducted by all participants accompanied by trainers. The community education program which was initiated by the Elementary School Teacher Education Study Program of STKIP Muhammadiyah Batang was carried out very well and the positive impression of all participants was the best program. The existence of training programs and mentoring of scientific writing is felt very useful by participants, because through this program teachers (participants) who follow this program get new knowledge in the creation of scientific papers, especially in the making of Class Action Research (CAR).